2019
DOI: 10.13083/reveng.v27i3.935
|View full text |Cite
|
Sign up to set email alerts
|

Análise Do Conforto Térmico No Estado Do Rio Grande Do Sul Utilizando Técnicas Geoestatísticas E Dados Das Normais Climatológicas

Abstract: A análise de dados climáticos permite a previsão de áreas com ocorrência do estresse calórico e auxilia na tomada de decisões quanto ao manejo ambiental adequado. O presente trabalho teve como objetivo analisar o conforto térmico no estado do Rio do Grande do Sul por meio de técnicas geoestatísticas e de dados das normais climatológicas (1961-1990 e 1981-2010). O estudo foi realizado para os meses de verão, em 18 municípios do Rio Grande do Sul. Os dados meteorológicos médios mensais de temperatura máxima (Tma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…Therefore, it is verified that the animals subjected to forced ventilation consumed more feed, confirming the results found by Oliveira et al (2019b), when assessing climate control systems for growing pigs. Brustolini & Fontes (2014) state that under temperature conditions above the upper critical temperature (UCT), the effects on pig weight gain is a factor of great relevance because, at each centigrade degree of increment there is a 55 g reduction in feed intake.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Therefore, it is verified that the animals subjected to forced ventilation consumed more feed, confirming the results found by Oliveira et al (2019b), when assessing climate control systems for growing pigs. Brustolini & Fontes (2014) state that under temperature conditions above the upper critical temperature (UCT), the effects on pig weight gain is a factor of great relevance because, at each centigrade degree of increment there is a 55 g reduction in feed intake.…”
Section: Resultssupporting
confidence: 83%
“…There was a high local thermal amplitude, with value of 13.22 °C in the external environment, with minimum recorded at 5 h and maximum recorded at 13 h ( Figure 1A). According to Oliveira et al (2019b), the range tolerated by adult pigs is 8.0 °C. Santos et al (2012) found a difference of 3.5 °C when reducing the thermal amplitude of a shed with pigs using forced ventilation associated with nebulization, compared to natural ventilation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation